Blood biomarkers to identify ischemic stroke etiologies. Issue 4 (July 2010) - García-Berrocoso, Teresa; Fernández-Cadenas, Israel; Delgado, Pilar; Rosell, Anna; Montane, Joan
Stroke is one of the main causes of death and disability in the world. However, there are still several medical limitations in stroke prevention, diagnosis and treatment. One promising field under investigation is the use of biomarkers to guide stroke etiology diagnosis and classification, since treatment differs among etiologic subtypes (cardioembolic, atherosclerotic and lacunar stroke) and many patients currently receive a diagnosis of undetermined stroke. In this article we update current knowledge about biomarkers related to specific stroke etiologies and discuss whether using a combination of biomarkers seems a feasible strategy for making an etiologic diagnosis in the acute phase of stroke. In the future, the use of these biomarkers will allow clinicians to rapidly guide other diagnostic tests and accelerate the onset of an optimal secondary prevention.